Miracles : the credibility of the New Testament accounts - Keener, Craig S., 1960- (Baker Academic, 2011)
This study presents the most thorough current defense of the credibility of the miracle reports in the Gospels and Acts. Drawing on claims from a range of global cultures and taking a multidisciplinary approach to the topic, Keener suggests that many miracle accounts throughout history and from contemporary times are best explained as genuine divine acts, lending credence to the biblical miracle reports. --from publisher description